P 78 Sonographic and electrophysiological characterization of peripheral nerves in patients with diabetes type 2. (May 2022) - Heiling, B.; Kobler, N.J.; Müller, N.; Grimm, A.; Kloos, C.; Axer, H.
Abstract : Introduction: Diabetic polyneuropathy is a significant complication of diabetes mellitus, occurring in approximately 20-30% of diabetic patients. Our objective is to characterize the peripheral nerves of patients with type two diabetes especially with nerve ultrasound because there have been inconsistent results regarding nerve enlargement in the past years. Methods: 75 patients with diabetes type 2 (with and without polyneuropathy) underwent clinical, sonographic (using the UPS Score), and electrophysiological evaluation. Results: Nerve ultrasound showed only few sites with nerve enlargement at non-compression sites. Our results confirmed increased cross-sectional areas (CSA) in peripheral nerves at compression sites as it was shown before by Pitarokoili and colleagues. First one-year follow-up examinations revealed an improvement of nerve enlargement after dietary change, weight reduction and change of diabetes medication. Conclusion: Diabetic polyneuropathy cannot be detected reliably by using the UPS Score, but the score is useful to exclude competing inflammatory demyelinating causes of neuropathy. CSA improvement after one year with dietary change, weight reduction and change of diabetes medication indicates that the result of these metabolic changes might be directly visible using nerve ultrasound. Further longitudinal studies are required to confirm our results.